NO reduction under diesel exhaust conditions over Au/Al2O3 prepared by deposition-precipitation method - Miguel, P.; Granger, P.; Jagtap, Neelam; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dujardin, Christophe (Journal of Molecular Catalysis A-Chemical, 2010)
Gold supported on alumina was prepared by urea deposition-precipitation method and compared to silver supported on alumina for the selective catalytic reduction of NO by hydrocarbons under lean conditions. The catalyst showed activity in the reduction of NO and 100% selectivity towards N-2 in the temperature range 300-350 degrees C. At higher temperature the NO conversion decreased due to competitive oxidative reactions of the reductants. XPS analysis confirmed the good stability of gold nanoparticles deposited on alumina. Infrared studies showed the formation of various adsorbed species (formates, carboxylates, ad-NOx and cyanide) on the catalyst surface. Addition of H-2 to the feed containing decane enhanced the formation of these species on the catalyst surface as well as the catalytic activity for the NO conversion to N-2. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Deposition-precipitation; Gold; In situ IR; NO reduction; XPS

Ceria-zirconia mixed oxides as thermal resistant catalysts for the decomposition of nitrous oxide at high temperature - Esteves, P.; Wu, Y.; Dujardin, Christophe; Dongare, Mohan K.; Granger, P. (Catalysis Today, 2011)
This present study deals with the development of thermally stable catalysts for the decomposition of nitrous oxide. There is actually a growing interest to minimise the emissions of nitrous oxide (N(2)O) as side-product from nitric acid plants due to a global warming potential of approximately 300 times higher than that of CO(2). Different strategies have already been implemented at industrial scale but they are still suffering from significant drawbacks essentially associated to a poor selectivity and sometimes a short lifetime in particular when the catalytic process is inserted downstream the ammonia burner. In those critical conditions, with high residual temperature of similar to 900 degrees C, significant surface and bulk reconstructions take place and then lead to drastic losses of specific surface area and related catalytic performances in the decomposition of N(2)O to N(2). Previous investigations performed in our laboratory revealed the potentiality of zirconia particularly after yttria incorporation [Appl. Catal. B 62 (2005) 236]. Novel developments of more stable ceria-zirconia based catalysts are reported in this study. Further stabilisation and enhancement in activity have been discussed on the basis of oxygen mobility related to structural properties. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ceria-zirconia based catalysts; Greenhouse gas; N(2)O catalytic decomposition; Nitric acid plant; Nitrous oxide

Deposition-precipitation versus anionic-exchange Au/Al2O3 catalysts: a comparative investigation towards the selective reduction of NOx - Nguyen, D. L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Catalysis Communications, 2012)
Catalytic properties of supported gold catalysts on gamma-Al2O3 prepared by a conventional deposition-precipitation method were compared with those obtained by anionic-exchange for the reduction of NOx by hydrocarbon under lean conditions that simulate Diesel engine exhaust gas. Interestingly, a catalytic activity enhancement is observed after thermal ageing under reactive conditions at 500 degrees C on anionic-exchanged samples which make them suitable for practical developments. On the other hand, the reverse trend is observed on the solids prepared by deposition-precipitation which deactivate at low temperature. Such changes in catalytic properties have been tentatively explained on the basis of textural and structural modifications taking place during thermal ageing under wet atmosphere. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Anionic-exchange; Au catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

Promising stability of gold-based catalysts prepared by direct anionic exchange for DeNO (x) applications in lean burn conditions - Nguyen, D. -L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Topics in Catalysis, 2013)
Supported gold catalysts on gamma-Al2O3 have been investigated in the catalytic reduction of NO (x) in simulated Diesel exhaust gas conditions. Different parameters have been examined essentially the mode of gold incorporation via classical deposition-precipitation and anionic exchange methods and the nature of the pre-activation thermal treatment. The resistance to thermal ageing under reactive conditions at 500 A degrees C was found completely different with a significant rate enhancement on anionic-exchange samples. Further comparisons also show that the nature of the pre-activation thermal treatment influences the extent of surface reconstructions during thermal ageing with a detrimental effect of reductive pre-treatment on the catalytic performances.
Keywords: Anionic-exchange; Au/Al2O3 catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

Rational preparation of Ag and Au bimetallic catalysts for the hydrocarbon-SCR of NOx: sequential deposition vs. coprecipitation method - More, Pavan M.; Nguyen, D. L.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Nuns, N.; Girardon, J. S.; Dujardin, Christophe; Lancelot, Christine; Mamede, Anne-Sophie; Granger, P. (Applied Catalysis B-Environmental, 2015)
This study emphasizes the importance of the preparation method for bimetallic Au-Ag catalysts supported on alumina in the selective reduction of NOx by hydrocarbons with gas feed compositions representative of diesel fuelled engine exhaust gas. An optimal balance between oxidative and reductive surface properties is obtained when Au and Ag are successively introduced. Significant re-dispersion processes take place when the catalyst runs at 500 degrees C leading to a gain in activity at low temperature and ascribed to a better interaction between Au and Ag species. Co-precipitation leads to a preferential formation of intermetallic Au-Ag particles which is detrimental to the catalytic performances. Aging at 500 degrees C leads to a significant particle sintering and a strengthening of the metallic character. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Au-Ag particles; Co-precipitation; DeNO(x) reaction; HC-SCR

Bimetallic Au-Ag/Al2O3 as efficient catalysts for the hydrocarbon selective reduction of NOx from lean burn engine exhaust - More, P. M.; Dongare, M. K.; Umbarkar, S. B.; Granger, P.; Dujardin, C. (Catalysis Today, 2018)
Catalytic properties of Au-Ag/Al2O3 catalysts, prepared by successive impregnation, have been investigated for the hydrocarbon selective catalytic reduction (HC-SCR) of NOx. The performances of pre-reduced and aged catalysts were evaluated on synthetic reaction mixtures with gas compositions representative of the exhaust of Diesel powered engines. An optimal 2 wt.% Ag loading was chosen and the order of introduction during sequential impregnation of Ag or Au on respectively pre-impregnated Au/Al2O3 and Ag/Al2O3 substrates was investigated revealing drastic changes on the catalytic properties after aging. XPS analysis shows a significant silver enrichment irrespective of the preparation route and aging conditions whereas ex situ UV-vis DRS analysis reveals significant electronic disturbances which reflect different interactions between Au and Ag in fresh and aged Au-Ag/Al2O3 and Ag-Au/Al2O3 catalysts. As a consequence, significant rate enhancements in NOx conversion were observed with the superior performance of Au-Ag/Al2O3 but a lower resistance to deactivation at high temperature explained by different behaviour towards redispersion/agglomeration processes highlighted from TEM observations. (C) 2016 Elsevier B.V. All rights reserved.

Enhanced selectivity of 3-D ordered macroporous Pt/Al2O3 catalysts in nitrites removal from water - Sekhar, A. C. Sunil; Zaki, A.; Troncea, S.; Casale, S.; Vinod, C. P.; Dacquin, J. P.; Granger, P. (Applied Catalysis A-General, 2018)
Tailored macroporous mesoporous alumina supports have been successfully prepared using a single hard templating approach. Pt nanoparticles, showing similar physico-chemical properties, were homogeneously dispersed throughout the different alumina frameworks as catalytic active phase for drinking water treatment. We demonstrated that careful modification of pore properties of the catalyst (size and connectivity) by pseudomorphic transformation can strongly modulate the reaction rate and selectivity through the limited access to Pt active sites within the alumina porous particles. Specifically, 3-D Ordered Macroporous Pt-Al2O3 catalysts with a high degree of interconnectivity yield to superior catalytic properties (enhanced activity and selectivity) over pure mesoporous counterparts in the hydrogenation of nitrites in water. We found that large pores (240 nm) interconnected with windows (110 nm) alleviate mass transfer limitations and clearly improve NZ selectivity. The findings of this study further suggest the possibility of engineering the pore architecture of the support to fine tune the selectivity for a particular reaction rather than investigating more on tuning the properties of the costly active metallic phase.

What news in the surface chemistry of bulk and supported vanadia based SCR‐catalysts: improvements in their resistance to poisoning and thermal sintering - Granger, P.; Siaka, H.W.; Umbarkar, S.B. (Chemical Record, 2019)
This paper reports a short review on the impact of poisoning effects and thermal aging on the reactivity of surface vanadate species on benchmark V2O5−WO3/TiO2 Selective‐Catalytic‐Reduction catalysts. A renewed interest of this SCR technology is related to its diversification notably as after‐treatment systems to treat the exhaust from Diesel engines with higher running temperature especially when SCR catalysts are coated on Diesel Particulates Filters. Particular attention is also paid to poisoning effects in conjunction with the progressive replacement of fossil fuels by bio‐fuels containing alkaline contaminants which drastically deactivate the catalyst through neutralization of strong acid sites. Most of the investigations show that better insight into the mechanisms of poisoning and aging processes is needed especially to understand the relative sensibility of various vanadate species. This could provide original guidelines to catalyst preparation and or the developments of more stable bulk systems as exemplified.